KAJIAN PSIKOLOGI SASTRA NOVEL BIDADARI BERMATA BENING KARYA HABIBURRAHMAN EL SHIRAZY DAN NILAI PENDIDIKAN KARAKTER TOKOH DALAM PERSPEKTIF PEMBELAJARAN BAHASA INDONESIA - Novia Rahmah Bastian; Suyitno Suyitno; Chafit Ulya (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
The purpose of this research is to describe and explain: (1) intrinsic element of novel Bidadari Bermata Bening; (2) psychological burden of the main character; (3) character education values; (4) the position of novel Bidadari Eye Bening by Habiburrahman El-Shirazy in Indonesian Language Learning perspective. This research was conducted by qualitative descriptive method and using psychology approach of literature. The results of this study indicate that: (1) each element of the novel has relevance with other elements so as to make the story coherent. (2) psychological analysis for the psychological burden of the main character using Sigmund Freud's theory of analysis which includes the three elements of personality namely id, ego, and superego. (3) the values of character education contained in the novel include religious, honest, tolerance, discipline, hard work, creative, independent, curiosity, respectful achievement, friendly / communicative, peace loving, social caring, and responsibility. (4) novel Bidadari Bermata Bening by Habiburrahman El Shirazy can be used as Learning material of Bahasa Indonesia.